Herida por arma de fuego con lesión de corazón y pulmón izquierdo. Informe de caso - Rivero León, Armando; Nuñez Calatayud, Margis; Hernández Liven, José Antonio (Mediciego, 2022)
Introduction: chest injuries were described for the first time around 1600 BC in the Edwin Smith Papyrus. The most frequent causes are traffic accidents and the use of firearms; less than 15% of those affected require definitive surgical treatment. Objective: to present the case of a person injured by self-harm with a firearm, with danger to life. Case presentation: white male patient, 25 years old, with a health history. He went to the Morón hospital emergency service after making a suicide attempt with a firearm, which caused a precordial injury. He arrived in a state of shock; chest x-rays showed the projectile and a concomitant left hemothorax. It was decided to perform an emergency anterolateral thoracotomy. Two holes were found; one in the left ventricle and one in the basal segments of the lower lobe of the left lung.After repairing the injuries and putting drainage in the thoracic cavity, the patient was transferred to intensive care, his condition evolved favorably, and he was discharged on the ninth day. Conclusions: the prognosis of cardiac injuries due to accidents with firearms and knives is serious. Whether it is not, depends on the combination of immediate transport, the resuscitation measures adopted in emergencies, and the severity of the anatomical damage to the organ found in the perioperative period. The work provided evidence on the importance of timely diagnosis and treatment as guarantees for a prognosis of survival with minimal complications